Association of Dietary Inflammatory Index (DII) and Depressive Disorders - Li R; Zhan W; Huang X; Liu Z; Lv S; Wang J; Liang L; Ma Y (Dove Medical Press, 2021)
Ruiqiang Li,1,* Wenqiang Zhan,2,* Xin Huang,1 Zhan Liu,1 Shuaishuai Lv,1 Jiaqi Wang,1 Luyao Liang,1 Yuxia Ma1 1Department of Nutrition and Food Hygiene, School of Public Health, Hebei Medical University, Hebei Province Key Laboratory of Environment and Human Health, Shijiazhuang, People’s Republic of China; 2School of Public Health, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuxia MaDepartment of Nutrition and Food Hygiene, School of Public Health, Hebei Medical University, Hebei Province Key Laboratory of Environment and Human Health, Shijiazhuang, People’s Republic of ChinaEmail mayuxia@hebmu.edu.cnAbstract: A lot of evidence shows that inflammation is related to the development of depression. However, the heterogeneity of depression hinders efforts to understand, prevent and treat this disease. The purpose of this comprehensive review is to summarize the links between inflammation and the established core features of depression, which show more homogeneity than the syndrome itself: overreaction to negative information, changes in reward processing, and cognitive control decline, and somatic syndrome. For each core feature, we first briefly outline its relevance to depression and neurobiological basis, and then review the evidence to investigate the potential role of inflammation. We mainly focus on the discovery of the experimental paradigm of exogenous inflammation. We concluded that inflammation may play a role in overreaction to negative information, altered reward responses, and physical symptoms. There is less evidence to support the effect of inflammation on cognitive control by standard neuropsychological measures. Finally, we discussed the implications for future research and recommendations on how to test the role of inflammation in the pathogenesis of heterogeneous mental illness.Keywords: dietary inflammatory index, depressive disorders, inflammation